Analysis of factors influencing pulmonary tuberculosis examination of household contacts of pulmonary tuberculosis patients in the working area of Nambo Public Health Center Kendari City - Histina Histina; Yusuf Sabilu; La Ode Muhammad Sety (Indonesian Journal of Health Science, 2026)
Tuberculosis (TB) remains a major global public health problem with a high disease burden, including in Indonesia, which ranks second worldwide. Active case finding through household contact screening is an essential strategy for TB control; however, its implementation is influenced by various factors. This study aimed to analyze the factors influencing pulmonary TB screening among household contacts of TB patients in the working area of Nambo Primary Health Center, Kendari City, in 2025. This study employed an analytic survey with a case-control design. The sample consisted of 54 respondents, including 27 cases and 27 controls, selected using total sampling. Data were analyzed using the chi-square test and binary logistic regression. The findings revealed a significant association between healthcare worker support (p=0.002; Exp(B)=6.525) and knowledge (p=0.015; Exp(B)=5.292) with pulmonary TB screening. Meanwhile, family support (p=0.406), were not significantly associated. Multivariate analysis indicated that healthcare worker support was the most dominant factor influencing TB screening among household contacts. The results highlight the crucial role of healthcare workers in improving screening compliance through education, assistance, and motivation. In addition, enhancing the knowledge of household contacts is essential to support early TB detection. Therefore, strengthening health promotion strategies and increasing the active involvement of healthcare workers in TB control programs at the primary healthcare level are highly recommended.